Penetapan Mata Rumah Parentah Dalam Sistem Pemerintahan Adat - Sarimanella, Welfri; Pietersz, Jemmy Jefry; Nirahua, Garciano (PATTIMURA Law Study Review, 2025)
The king of a traditional country is usually appointed and elected directly by the traditional community of the traditional country, usually there is one or more clans (fam) that are descendants of the king (mata ruma parenta). With the issuance of Ambon City Regional Regulation Number 10 of 2017 concerning the Appointment, Election, Inauguration and Dismissal of the Head of the Country Government (hereinafter referred to as Regional Regulation no. 10 of 2017), the traditional community through the Saniri Negeri determines the mata rumah parentah and is made in a country regulation. The research method used is normative legal research. The normative legal research method is a library legal research conducted by examining library materials or secondary data. This research was conducted in order to obtain materials in the form of theories, concepts, legal principles and legal regulations related to the subject of Language. The use of legal material sources consists of primary and secondary legal materials to discuss the formulation of the problem. The results of the study show that: (1) the determination of the house of the panrentah has been in accordance with the laws and regulations as per the Ambon City Regional Regulation Number 10 of 2017 concerning the appointment, election, inauguration and dismissal of the head of government. Which is procedurally implemented by the Saniri Negeri through a voting system. This system has also been regulated in the Central Maluku Regency Regional Regulation Number 04 of 2006 concerning guidelines for organizing the Saniri Negeri or the State Deliberative Body; (2) Law as a regulation of human behavior that is mandatory and must be obeyed. The legal consequences if the determination of the house of the parentah in a traditional country is the postponement of the election of the candidate for head of the state government (King).